K-MEANS CLUSTER ANALYSIS OF SUB-DISTRICTS IN SIDOARJO BASED ON LONG-TERM CONTRACEPTIVE METHOD - Cempaka Puspita Siwi; Yasmine Nurfirdaus (Universitas Airlangga, 2020)
The success of the Family Planning program can be measured from the ratio of the use of the Long-Term Contraceptive Method by the couples of childbearing age in each region. The approach used in the Family Planning program is a regional approach, so this study aimed to group sub-districts based on the proportion users of the Long-Term Contraceptive Method by couples of childbearing age in Sidoarjo in 2018. This study was non-reactive study, which is a type of research using secondary data. The data source came from the Report of the Office of Women's Empowerment and Child Protection, Family Planning Sidoarjo in 2018. This study used cross-sectional design with the K-Means Clustering model data analysis. The results of this study produced three regional clusters: Cluster 1 with a low success rate sub-districts category with 8 sub-districts; Cluster 2 with a medium success rate category that has 6 subdistrict members; and Cluster 3 with a high success rate category consisting of 4 sub-districts in Sidoarjo. Based on the study results, broad accessibility was needed to obtain information so that the level of the Long-Term Contraceptive Method users in Sidoarjo increases.